2006
DOI: 10.1152/ajpheart.01237.2005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of osmotic compression on sarcomere structure and myofilament calcium sensitivity of isolated rat myocardium

Abstract: Farman, Gerrie P., John S. Walker, Pieter P. de Tombe, and Thomas C. Irving. Impact of osmotic compression on sarcomere structure and myofilament calcium sensitivity of isolated rat myocardium. Am J Physiol Heart Circ Physiol 291: H1847-H1855, 2006. First published June 2, 2006 doi:10.1152/ajpheart.01237.2005.-Changes in interfilament lattice spacing have been proposed as the mechanism underlying myofilament length-dependent activation. Much of the evidence to support this theory has come from experiments in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 38 publications
3
64
0
Order By: Relevance
“…As explained in detail by Tyska and Warshaw (28) ); and 3) the ratio k ÀADP /k þATP , which represents the concentration of MgATP producing half the maximal myosin detachment rate (i.e., [MgATP] 50 ).…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…As explained in detail by Tyska and Warshaw (28) ); and 3) the ratio k ÀADP /k þATP , which represents the concentration of MgATP producing half the maximal myosin detachment rate (i.e., [MgATP] 50 ).…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…One proposed mechanism is that titin strain imposes a radial force on the sarcomere lattice to modulate inter-filament spacing thus leading to altered myosinactin interaction and myofilament Ca 2+ sensitivity [12,19]. However, X-ray diffraction studies on skinned myocardium have questioned the role of interfilament spacing in directly modulating myofilament Ca 2+ sensitivity and proposed that the disposition of myosin heads was a more predictive index [17]. Several other factors, such as phosphorylation of MLC-2 or cMyBP-C are also known to affect the arrangement of myosin heads.…”
Section: Passive Tension-based Modulationmentioning
confidence: 99%
“…Part of this effect may be due to reduced interfilament lattice spacing with stretch, which may increase the probability of myosin binding to actin to yield more forcegenerating cross-bridges that activate the thin filament [31,39]. A recent study has shown that interfilament spacing alone cannot explain changes in Ca 2+ sensitivity [17]. It now seems more likely that Ca 2+ sensitivity is determined by changes in the structure of myosin filaments [17,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently found that TnI-Thr144 per se is able to impart length-dependent properties onto the cardiac sarcomere, while a proline at that position virtually eliminates myofilament length dependency [75]. These results suggest that myofilament-length-dependent activation has, at its basis, a signal transduction pathway that includes Tn-Tm-actin signaling rather than a more direct mechanism involving myosin-actin affinity modulated by inter-filament spacing [19,20,40]. The underlying molecular mechanisms, however, are as of yet still largely unknown.…”
Section: Troponin Imentioning
confidence: 99%